Positive Effects of a Short-Term Dog-Assisted Intervention for Soldiers With Post-traumatic Stress Disorder—A Pilot Study - Beetz, Andrea; Schöfmann, Ira; Girgensohn, Roland; Braas, Roger; Ernst, Christiane (Frontiers in Veterinary Science, 2019)
Posttraumatic stress disorder (PTSD) is diagnosed in 3% of German and 14-16% of US military following abroad deployment abroad. The treatment of PTSD in soldiers is often challenging and thus new, additional interventions supporting traditional trauma therapy are employed, like animal-assisted interventions (AAI). In thisa pilot study, 29 soldiers with PTSD received four sessions of three hours once a week of dog-assisted intervention in addition to inpatient standard treatment at the military hospital, while the control group of 31 soldiers with PTSD received standard treatment only. The dog-assisted intervention sessions included a walk, different play and grooming activities and just relaxing together towards the end. What was new in our approach was that the AAI sessions were delivered by military personnel, military dog-handlers with their own dogs (either military or privately owned). Data on psychiatric symptoms, perceived stress, work and social life, and the therapeutic relationship were answered before the first AAI session, during the days following the last AAI session, one month later, and three months later. Only the intervention group also answered a questionnaire on trauma confrontation, consumption of alcohol/drugs, mental wellness and perceived stress each week during intervention. Analyses showed a trend for worse values in work and social adjustment in the control group and a significant trend toward better values in the intervention group. On the other parameters differences between control and intervention group were not significant. The mental wellness of the intervention group improved over the four weeks of therapy, particularly regarding the ability to experience joy. There was no clear trend for perceived stress, but the relationship to the dog handler improved significantly over the course of the intervention. This is noteworthy in patients with PTSD who usually have difficulties trusting others, especially new people. Keeping in mind that the AAI took place only four times, our findings point towards the value of dog-assisted interventions. With a longer treatment period the positive effects and trends might become more distinct.